Cultures of E/valuation on the Social Web. A very short introduction to the special issue - Berenike Herrmann; Noah Bubenhofer; Daniel Knuchel; Simone Rebora; Thomas Messerli (Journal of Cultural Analytics)
The aim of the special issue is to present theory-conscious studies of selected facets of digital cultures of evaluation across a broad range of discourses on the social web. At the same time, bringing together papers from linguistics, literary studies, and digital humanities, it is our aim to take stock of common denominators, but also differences, in method and theory, instilling discussion for a cross-disciplinary data-driven and data-intensive inquiry of valuation and evaluation within “data humanities”. The types of discourse covered will include online lay book reviews on platforms such as Goodreads and LovelyBooks, as well as reviews of non-literary “products“ such as cooking recipes, restaurant reviews, and concerts.